Understanding business offenders: a comparative analysis of workplace deviance, convenience and control - Gottschalk, Petter (Berghahn Books, 2025)
"Focusing on understanding business offenders through an exploration of workplace deviance and crime, this book closely examines a number of illustrative contemporary case studies and underpins the analysis of original comparative fieldwork, with an interdisciplinary approach, which informs, develops, and augments the existing literature on white-collar criminology. The book contends, inter alia, that the traditional centrality of the individual actor within narratives of white-collar offending has receded somewhat in recent years despite being a founding artifact within its late twentieth- century discourse, and that therefore a detailed reassessment is overdue"--